Um estudo semiótico do aplicativo digital Livox: mediação e alfabetização de estudantes com Transtorno do Espectro do Autismo. - Silva, Josiane Almeida da (2022)
Public policies, aimed at education, defend the right to learning as a condition for human development and aim to make the school, as well as other spaces of specialized educational assistance, more inclusive environments. A challenge faced by schools is to promote the literacy of people with disabilities and with Autism Spectrum Disorder (ASD), due to their singularities. Thinking about it, the Alternative and Expanded Communication Systems (AECS) and digital information and communication technologies (DICT) contribute to the learning and inclusion of people with disabilities and disorders, as they facilitate the development of linguistic and cognitive skills. Studies on this topic need to be expanded. This research had as object of study the digital application (App) Livox. This resource was adopted by the Department of Education of the city of Recife – Pernambuco – with the purpose of helping the development of communication and interaction of people with speech deficits. The App has semiotic resources that facilitate the interaction and learning of people with or without disabilities through written texts, images, audios and videos. Our general objective: to analyze whether the semiotic resources present in the Livox application, proposed for mediation in the literacy of students with ASD, meet the semiotic categories of Visual Design Grammar (VDG), as well as the principles of the alphabetic writing system (AWS) . The discussions were based on inclusive education represented by Lopes and Dal'Igna (2007), Glat and Blanco (2007), Orrú (2012), on multiliteracies, Rojo and Moura, (2012), Mattar (2010). On digital technologies, we turn to Ribeiro (2010; 2021). As for semiotics and social semiotics, we are based on Santaella (2003; 2005), Kress and van Leeuwen (2006). To deal with the appropriation of the Alphabetic Writing System (SEA), we base ourselves on Soares (2016, 2020); Morais (2012; 2019). About TEA, we use the studies of Schwartzman and Araújo (2011), Orrú, (2012; 2011), Volkmar (2019); Borges; Walnut (2018). This is an exploratory, analytical-descriptive study with a qualitative approach. Data were collected from two schools in the Recife – Pernambuco education network. The instruments were used: electronic questionnaire (Google forms), answered by four teachers from Specialized Educational Assistance (SEA) working in Multifunctional Resource Rooms (MRR) to visualize their understanding of the use of technologies in their practice. The responses were analyzed following the assumptions of Content Analysis, Bardin (2015); we analyzed the Livox user manual, footage and photos of the App screens. The screens were analyzed in light of the VDG and the principles of the Alphabetic Writing System (AWS). For this purpose, two analysis tables were prepared, containing the VDG and AWS categories. The results showed that the App has elements that fit into the VDG categories and can favor the engagement of people with AWS. It also contains elements that can be used to promote the literacy of these students, since they meet the AWS principles. The research showed that Livox was only used to facilitate student communication. Participants viewed only one of the aspects made possible by the App – alternative and expanded communication. It would be relevant for students, in the literacy process, to benefit from the various opportunities offered by this App.